2015
DOI: 10.1016/j.jvs.2015.01.039
|View full text |Cite
|
Sign up to set email alerts
|

Standard duplex criteria overestimate the degree of stenosis after eversion carotid endarterectomy

Abstract: The presence of hemodynamically significant carotid artery restenosis may be overestimated by standard duplex criteria after eCEA and perhaps after pCEA. Insufficient information currently exists to determine what PSV does correspond to hemodynamically significant restenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…[34][35][36][37][38] Emerging data suggest the need for similar revisions to velocity criteria after CEA; however, additional studies need to be performed before firm recommendations can be made. 40,41…”
Section: Risk Factors For Carotid Restenosismentioning
confidence: 99%
“…[34][35][36][37][38] Emerging data suggest the need for similar revisions to velocity criteria after CEA; however, additional studies need to be performed before firm recommendations can be made. 40,41…”
Section: Risk Factors For Carotid Restenosismentioning
confidence: 99%
“…1,6,14 Therefore, standardizing cut-off values for parameters is of great significance for patient screening and evaluating clinical treatment. However, in the early 1990s, some studies [7][8][9] reported that diagnostic criteria assessed using CDU overestimated the stenosis degree for bilateral carotid artery stenosis. In 1998, van Everdingen et al 7 revealed that this overestimation was due to one side of the ICA being occluded and causing blood flow to increase on the other side of the ICA with carotid artery stenosis; this was confirmed by cerebral blood flow perfusion on MRI.…”
Section: Discussionmentioning
confidence: 99%
“… 7 , 8 Moreover, following the eversion technique for CEA, the degree of restenosis evaluated by CDU based on previous blood flow velocity criteria was overestimated. 9 However, the reason for this phenomenon is rarely mentioned in previous literature. In the clinical practice of our center, we have noticed that the anterior communicating artery patency will have a certain impact on the flow velocity measurement of the intracranial segment of the internal carotid artery (ICA).…”
Section: Introductionmentioning
confidence: 99%
“…The high variability of flow velocity thresholds suggests that no single duplex ultrasound parameter can be used to reliably determine the degree of ICA restenosis after CAS or CEA. Similar to the assessment of the severity of stenosis in native ICA ( 10 ), combinations of different flow velocity criteria (PSV, EDV, or ICA/CCA ratio), B-mode and color imaging, and parameters influencing cerebral hemodynamics should be considered for a more accurate evaluation of the degree of restenosis after CEA and CAS ( 21 ).…”
Section: Discussionmentioning
confidence: 99%